The influence of classroom management on ability mathematics literacy of class vii students - Safitri Siregar, Amalia; Ubudiyah Siregar, Sakinah; Ariani Hrp, Nurlima (Educenter : Jurnal Ilmiah Pendidikan, 2024)
The research was conducted with the aim of finding out the effect of classroom management on students' literacy skills. Classroom management is carried out to achieve effective learning goals so that it can improve students' abilities in learning mathematics. This research is quantitative research, the population is class VII students of SMP Negeri 2 Rantau Selatan. and took a sample of 30 students, the data collection technique used a questionnaire technique, using a data analysis technique, namely linear regression analysis. From the results obtained in the classroom learning model, it is very important for teachers to strive to create good and enjoyable teaching and learning conditions. In this study, classroom management was quite good, but students' mathematical literacy skills were still lacking due to difficulties in solving mathematical problems. So it can be said that classroom management can influence the mathematical literacy skills of students at SMP Negeri 2 Rantau Selatan.